Towards a Green Constitution: Normative Reflection on Indonesia's 1945 Constitution in Global Comparative Context - Muh Farhan Arfandy; Nurul Zashkia (Lembaga Penelitian dan Pengabdian kepada Masyarakat UPJ, 2026)
This article analyzes the incorporation of environmental norms into constitutional law, focusing on the 1945 Constitution of the Republic of Indonesia within a comparative constitutional framework. Amid worsening global ecological degradation, the study investigates the extent to which the right to a healthy environment is recognized as a constitutional right and enforceable through legal mechanisms. Article 28H(1) and Article 33(4) of the 1945 Constitution reflect normative commitments to sustainable development, though in a general and non-justiciable form. Employing normative juridical and comparative legal methods, the study evaluates selected jurisdictions—Portugal, France, Ecuador, and India—which exhibit more progressive and enforceable environmental constitutionalism. The findings reveal that Indonesia's constitutional provisions remain insufficient in terms of clarity, institutional support, and judicial applicability. Therefore, this paper recommends a constitutional refinement through detailed and justiciable environmental provisions, accompanied by institutional guarantees. Strengthening environmental constitutionalism is essential to ensure intergenerational justice and ecological integrity within the framework of constitutional democracy..